Investigation of Calcium Oxide–Impregnated Zeolite Catalyst Toward Catalytic Pyrolysis of Oil Palm Empty Fruit Bunch: Bio-oil Yields, Characterizations, and Kinetic Study - Lim, Huei Yeong; Suzana, Yusup; Acda, Menandro N.; Lai, Bridgid Fui Chin; Elisabeth, Rianawati; Pornkamol, Unrean; Yiin, Chung Loong; Quitain, Armando T.; Suttichai, Assabumrungrat (Springer, 2023)
This work investigated the in situ catalytic pyrolysis of oil palm empty fruit bunch using CaO-impregnated zeolite (CaO/HZSM-5) catalyst. An optimum point was obtained via central composite rotatable design at reaction temperature of 567.10 °C, catalyst loading of 3.22 wt%, and CaO loading of 1.25 wt%, with an expected bio-oil yield of 35.31 wt%. Validation runs’ experimental yield was 37.59 ± 1.74 wt%, indicating reliability of the condition. The impregnated catalyst was characterized, and CaO was observed to be successfully impregnated onto HZSM-5 with minor degradation on the catalyst structures. The bio-oil produced through catalytic pyrolysis had increased 16.102 wt% water content, and also lower acid content by 8.02%, and higher aromatic content by 18.86% as compared with non-catalytic pyrolysis, possibly contributed by the combined catalytic effect of CaO/HZSM-5 catalyst via deoxygenation and neutralization reactions. Kinetic study using Coats-Redfern method indicated the decrement of activation energy and frequency factor by 2.14% and 49.17%, respectively, at reaction order of three with addition of CaO/HZSM-5 catalyst. Similar reductions in activation energies in presence of CaO/HZSM-5 catalyst was observed in model-free methods, and the activation energies gradually increased with process conversion due to differences in valorization temperatures of hemicellulose (300 °C), cellulose (340 and 390 °C), and lignin (> 400 °C).